Extended-spectrum β-lactamase (ESBL) polymerase chain reaction assay on rectal swabs and enrichment broth for detection of ESBL carriage. Issue 3 (March 2018) - van den Bijllaardt, W.; Janssens, M.M.; Buiting, A.G.; Muller, A.E.; Mouton, J.W.; Verweij, J.J.
Summary: Background: Extended-spectrum β-lactamase (ESBL) screening and contact precautions on patients at high risk for ESBL carriage are considered important infection control measures. Since contact precautions are costly and may negatively impact patient care, rapid exclusion of ESBL carriage and therefore earlier discontinuation of contact precautions are desired. Aim: In the present study, the performance of an ESBL polymerase chain reaction (PCR) targeting bla CTX-M genes was evaluated as a screening assay for ESBL carriage. Methods: Two methods were assessed: PCR performed directly on rectal swabs and PCR on enrichment broth after incubation overnight. The reference standard was culture of ESBL-producing Enterobacteriaceae on selective agar after overnight enrichment and confirmation by the combination disc diffusion method. Microarray was used for discrepancy analysis. A secondary analysis was performed to evaluate the added value of including a bla SHV target in the PCR. Findings: A total of 551 rectal swabs from 385 patients were included, of which 28 (5%) were ESBL positive in culture. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 86%, 98%, 67%, and 99%, respectively, for PCR directly on swabs, and 96%, 98%, 75%, and 100%, respectively, for PCR on enrichment broth. Adding a bla SHV target to the assay resulted in a lower PPV without increasing the sensitivity and NPV. Conclusion: Screening for ESBL by PCR directly on rectal swabs has a high negative predictive value, is up to 48 h faster than traditional culture and therefore facilitates earlier discontinuation of contact precautions, thereby improving patient care and saving valuable resources in the hospital.